Thermal Decomposition Kinetics of Cobalt(II) and Nickel(II) Complexes of Substituted Isoxazole and their Antibacterial Activity - Manohara, Y.N.; Nayak, P.V.; Mohan, S. (Asian Journal of Chemistry, 2012)
5-Amino-3(4-dimethyl amino phenyl) isoxazole-4 carboxylic acid complexes of cobalt(II) and nickel(II) have been subjected to thermal decomposition studies in air using TG and DTG techinique. The kinetic Parameters for all the stages of decomposition of these complexes were computed by a weighted least squares method-the Coats-Redfern equation.